O impacto do diagnóstico pré-natal de anomalia fetal: estratégias de enfrentamento utilizadas pelas gestantes - Nunes, Tatiane Santos [UNIFESP] (2015)
After the development of techniques in fetal evaluation, the use of a prenatal diagnosis of fetal anomalies has become a reality. With the diagnostic possibilities, it arouses the concern about them in relation to pregnant women and to their families. The announcement of a fetal anomaly causes a state of ?post-traumatic stress?, because it represents an immediate or later response towards a stressful event or situation, and the strategies of coping are strictly linked to the subjective stress generated in the pregnant women as a result of prenatal diagnosis of fetal malformation, both with viability and inviability prognostics. OBJECTIVE: To evaluate the impact of fetal anomaly diagnosis and strategies of coping used by pregnant women resulting from this stressful event, and to compare the coping strategies subsequent to viable and inviable fetal anomaly diagnosis. METHODOLOGY: This is a transversal study of quantitative analysis, developed in a Fetal Medicine ambulatory in São Paulo (SP), Brazil, between January 2014 and January 2015. The sample was composed of 120 pregnant women with the diagnosis of fetal malformation subdivided into two groups: viable and inviable fetuses. The data collection was performed in two phases: the first one at the admission process of the pregnant women in the ambulatory, after the pregnant women signed the Informed Consent Form; and the second one, after they took part in medical consultation of reproductive genetic counseling and at least in two psychoprophylactic consultations. A questionnaire for obtaining de socioeconomic and demographic data and the coping inventory were used. Chi square test, Fisher?s exact test or likelihood ratio were used in order to compare the categorical variables between viable and inviable. Student?s t test was used to compare the continuum variables between viable and inviable and, if necessary, variance analysis was also used. RESULTS: The women who were interviewed identified themselves as white in 50.8% of the cases; 58.3% were married or stable union; 59.2% presented high school level; 47.8% were Catholics; and 55,8% refered themselves as housewives. Regarding the coping strategies, it was possible to verify the social support (factor 4) as the more common coping factor used by the pregnant women, followed by the positive re-evaluation (factor 8), which the strategies that received a highlight were ?I had professional support?, and ?I prayed?. When compared both groups, a significant difference with higher score of the self-control strategy (factor 5) in the pregnant women presenting fetal inviability diagnosis, rather than in the viable fetus pregnant women, was found. CONCLUSION: The pregnant women who received the diagnosis results of fetal anomaly used more frequently the strategies focusing on the social support and on positive re-evaluation. It became evident the tendency of self-control in the group of pregnant women with inviable fetuses.